1973
DOI: 10.1037/h0034589
|View full text |Cite
|
Sign up to set email alerts
|

Listening and note taking: II. Immediate and delayed recall as functions of variations in thematic continuity, note taking, and length of listening-review intervals.

Abstract: Two experiments were conducted in which subjects listened to a passage divided into six segments of 5 minutes each. Manipulations were made of thematic relatedness of content, listen-study intervals, and note taking. More ideas were recalled when note taking was not permitted and when the material was on different topics or unconnected than when the material was on the same topic and/or connected. These effects were noted especially on a delayed-recall test administered 1 week following the listening period. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(40 citation statements)
references
References 10 publications
1
37
0
Order By: Relevance
“…Finally Frase (1969) found that varying passage organization required subjects to vary their information processing activities; as a result subjects retained some passage content better than others. This last study suggests a particular explanation for the results we have described above and also possibly the results of DiVesta and Gray (1973). When subjects are given no organizational information in the form of advance organizers or passage structure (whole condition) they are forced to carry out activities aimed at generating their own structure for the passage presented.…”
Section: Serial Position For Recall Performancementioning
confidence: 53%
See 3 more Smart Citations
“…Finally Frase (1969) found that varying passage organization required subjects to vary their information processing activities; as a result subjects retained some passage content better than others. This last study suggests a particular explanation for the results we have described above and also possibly the results of DiVesta and Gray (1973). When subjects are given no organizational information in the form of advance organizers or passage structure (whole condition) they are forced to carry out activities aimed at generating their own structure for the passage presented.…”
Section: Serial Position For Recall Performancementioning
confidence: 53%
“…This somewhat startling comment would have been dismissed had it not coincided so well with our findings. The issue was raised strikingly again in DiVesta and Gray's (1973) recent finding that their scrambled passage was remembered significantly better than a completely logical ordering of the passage. While they explained their finding as due to release from proactive inhibition the general argument we will now advance would also account for their finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the listener is to have a complete record of the lecture (one that can subsequently be accurately decoded), either some way of encoding the message other than spelling out each word completely must be used (e.g., abbreviation, speedwriting, shorthand) or the lecturer (perhaps in response to a signal from the listener) must speak very slowly or repeat the message. Although note taking during a lecture has been shown to enhance learning (DiVesta & Gray, 1973), information is lacking about both the effect of (1) message variables (e.g., speed and structure of the lecture) on the way in which the listener graphically encodes it and (2) the method of encoding on recall. Future research on these problems seems desirable.…”
Section: Discussionmentioning
confidence: 99%